Evaluation of surface integrity in cryogenic cylindrical grinding for automotive components (2022)
The automotive industry is a vital sector of the global economy and the well-being of people. Its production exceeds 1.9 trillion euros, generating more than 8 million jobs worldwide. Due to its large production quantities and high-quality requirements, manufacturing lines are forced to work with production capacities close to Cpk=1.67$. To maintain these production standards, some critical mechanical components with tolerances around IT5 to IT6 must overcome high surface integrity requirements, for example, surfaces without white-layer and with Ra roughness no higher than 0.32 µm. To achieve these surface features in finishing processes, such as grinding, cooling and lubricating fluids are used to reduce the temperature and friction between the grinding wheel and the workpiece. Cutting oils and synthetic water-miscible coolants are the most common products. Although these products have been used for decades, it has been proven that they can generate health issues and environmental problems. Reducing these polluting fluids with environmentally friendly fluids in grinding operations could contribute significantly to protecting the environment and guaranteeing healthy workplaces. For these reasons, this Ph.D. thesis aims to analyze the effects of cryogenic grinding on the surface integrity of 27MnCr5 steel, a material widely used to manufacture automotive gearbox components. To achieve this objective, experimental tests using several cooling strategies with LN2 were developed, in which the surface integrity was compared to conventional grinding, and optimal process windows were produced. With the optimal conditions selected, fatigue and tribological specimens were manufactured and tested to validate the performance of the cryogenic ground samples versus the conventional process. Additionally, with the experimental results, data-driven models were developed to explain and predict the variation in the surface roughness distribution when cryogenic strategies are used. Finally, the results showed that the cryogenic systems with LN2 could be an alternative in the grinding process; therefore, a technical and economic analysis was developed, considering the most relevant challenges for its implementation in the automotive industry.